DIGITAL TRUST MARKETING AND PREDICTIVE PATIENT ENGAGEMENT IN THE HOSPITAL POST-PANDEMIC ERA - Nur Farida; Siti Nur Qomariah; Khairul Azmi Abd Kadir (DIVERSITY Logic Journal Multidisciplinary, 2026)
Background. Hospital marketing management has shifted significantly in the digital era, particularly after the COVID-19 pandemic, where patients increasingly rely on online information, social media credibility, and digital trust before choosing healthcare services. However, previous studies predominantly focused on traditional hospital marketing dimensions such as service quality, satisfaction, and brand image, while limited research integrates predictive artificial intelligence (AI)-based communication with patient digital trust and behavioral engagement. Research Purpose. This study aimed to analyze the influence of AI-driven marketing communication, digital trust, electronic word-of-mouth (e-WOM), and perceived personalization on patient engagement and hospital service selection intention. Research Method. A quantitative cross-sectional design was conducted involving 420 respondents from urban healthcare consumers in Indonesia, selected using purposive sampling. Instrument of AI-Driven Communication, Electronic Word-of-Mouth (e-WOM), Personalized Digital Communication, Patient Engagement, Digital Trust, Hospital Selection Intention, and Patient Loyalty using structured questionnaires. Data were analyzed using Structural Equation Modeling (SEM-PLS). Findings. AI-driven communication significantly affects digital trust (? = 0.681; p < 0.001), while digital trust strongly influences patient engagement (? = 0.592; p < 0.001). Furthermore, patient engagement mediates the relationship between e-WOM and hospital selection intention. Personalized digital communication also demonstrated a significant positive effect on patient loyalty. Conclusion. Introducing an integrated predictive digital marketing framework in hospital management and practically by offering strategic insights for hospital administrators to optimize AI-based patient-centered marketing systems. Future hospital competitiveness increasingly depends on digital trust ecosystems and intelligent communication strategies.